Country Club area, general view of a columned house, Brookline, Massachusetts, 1 of 2. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
General exterior view of a house in the Country Club area of Brookline, Massachusetts. One of several slides taken in this area, and one of two of this subject.; Caption on image: Columned House Brookline, MA Mar 75 Country Club area.; Binder Number 4. Pocket Number: 2.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1975-03.; Apply to the DCA for access to the physical slides.